Should I Take It or Should I Not? Exploration of Students’ Course Choice as a Product - Goknil N. Kocak; N. Serdar Sever (International Review of Management and Marketing, 2011)
This study aims to explore the components of students’ course selection process and overlooking these components from marketing perspective. Three focus groups were administered. Data revealed that the focus groups participants’ responses are congregated in two main categories: (1) WOM related evaluations. (2) Official concerns based evaluations. The WOM related evaluations were emerged as follows; (1.1) instructors’ in-class performance, (1.2) the degree of attractiveness of course-related virtual environment, (1.3) the toughness of course assignments and their grading policies. Official concerns based evaluations were surfaced as follows; (2.1) level of academic and practical experience of instructors (2.2) the use of computer-enhanced learning technologies. Like consumer purchase decision process it is observed that, students too seek reliable information and gather information mainly from senior students in the form of WOM activities; and courses and instructors’ performance factors which are counterparts of product and services in academia are evaluated based on information in WOM activities.